Pharmacokinetics of generic and trade formulations of lamivudine, stavudine and nevirapine in HIV-infected Malawian children - Corbett, Amanda H. (2010)
OBJECTIVE: Evaluate the pharmacokinetics (PK) of lamivudine (3TC), stavudine (d4T), and nevirapine (NVP) in HIV-infected Malawian children receiving quartered tablet multiples of Triomune 40™ (GT) compared to individual generic (GL) and trade (TL) liquids DESIGN: prospective, randomized, 3-way crossover study METHODS: Subjects [8-<12kg;18-<22kg; or 28-<32kg] taking Triomune 40™ were recruited and randomized to receive GT twice daily (¼, ½, or ¾ tablets using Malawi treatment guidelines); GL twice daily (in the equivalent dose of GT), or TL twice daily (dosed using weight and age from DHHS Pediatric treatment guidelines). After 10 days of one formulation, 6-hour PK sampling was performed, and subjects crossed over to subsequent formulations. C(0h), AUC(0-6h), C(max,) and T(max) were generated for each antiretroviral (ARV). RESULTS: 7 male and 11 females (6 in each GT dosing group) with median (range) age of 7.2 (1.3-13.6) yrs, 19 (9-30.5) kg, and 109 (75-132) cm were recruited. Combining all subjects, no difference in pharmacokinetics was noted among the formulations for all drugs. However, subjects in the ¼ GT dosing group had lower 3TC exposures than with the GL or TL (3TC AUC(0-6h) = 1102, 1720, 2060 hr*ng/mL respectively; p<0.005) and had more subtherapeutic NVP C(0h) (10 of 13 occasions, versus ½ and ¾ tablet groups). Compared to western pediatric cohorts, Malawians had concentrations 30-40% lower for 3TC and d4T and 50% higher for NVP. CONCLUSIONS: Quartered multiples of Triomune 40™ are appropriate for children 18-<22kg and 28-<32kg . However, alternative formulations are suggested in children 8-<12kg.